Argumen Pemberdayaan Perempuan dalam Islam - Dody Riyadi HS (Jurnal Bimas Islam, 2015)
Abstract Through the Prophet Muhammad and the long history of Islamic civilization, where women like Khadija contribute significantly, Islam has a very real practice of the women empowerment. In a prophetic history, women actively involved in the life and prophetic as the messenger of God. Through the Quran, Islam introduced a variety of emancipatory concepts, such as libas and deliberation, as opposed to various forms of discrimination and exploitation against women. Islam and empowerment are two words that can not be separated. Islam, from any angle it interpreted, implies empowerment, and therefore, contrary to the actions of ignorant of any subordination of women. Abstraksi Melalui Nabi Muhammad dan sejarah panjang peradaban Islam, di mana perempuan seperti Khadijah ikut berkontribusi secara signifikan, Islam telah sangat nyata mempraktikkan pemberdayaan perempuan. Dalam sejarah kenabian, perempuan terlibat aktif dalam kehidupan dan kenabian utusan Tuhan. Lewat Al-Qur’an, Islam memperkenalkan berbagai konsep emansipatif, seperti libas dan musyawarah, yang bertentangan dengan berbagai bentuk diskriminasi dan eksploitasi terhadap perempuan. Islam dan pemberdayaan merupakan dua kata yang tak dapat dipisahkan. Islam, dari sudut manapun ia diartikan, mengandung makna pemberdayaan, dan karena itu, bertentangan dengan tindakan jahil apa pun yang menyubordinasikan perempuan.